2024
DOI: 10.5051/jpis.2203240162
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative survival rate of dental implants with micro-threads: a long-term retrospective study

Abstract: Purpose This study aimed to evaluate the long-term cumulative survival rate (CSR) of dental implants with micro-threads in the neck over a 10-year follow-up period and to examine the factors influencing the survival rate of dental implants. Methods This retrospective study was based on radiographic and dental records. In total, 151 patients received 490 Oneplant ® dental implants with an implant neck micro-thread design during 2006–2010 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In this study, they found 30 failures out of 300 implants, with an overall success rate of 98%. Nam et al [5] found that the dental implants had a 97.9%. The customer satisfaction rates [CSRs] for both external and internal CSRs were 98.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, they found 30 failures out of 300 implants, with an overall success rate of 98%. Nam et al [5] found that the dental implants had a 97.9%. The customer satisfaction rates [CSRs] for both external and internal CSRs were 98.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the researchers looked at nine different things: [1] whether the patient was male or female, [2] how old the patient was when they got a dental implant, [3] whether the patient had some or all of their teeth missing in their lower jaw, [4] where in the jaw the implant was placed [front or back], [5] whether the implant was put in right away or after a delay, [6] the size and type of implant used, [7] the quality of the bone in the jaw, [8] the type of false teeth used, and [9] whether one or more implants were put in. We collected information about the implants when they were put in or when the artificial teeth were installed.…”
Section: Study Variablesmentioning
confidence: 99%